Evaluación del “Pago en función de la calidad” de Base Granular y Mezcla Asfáltica para la construcción del pavimento de la carretera Costanera Sur - Fernández-Mesén, Denis (Instituto Tecnológico de Costa Rica, 2010)
The present work consists of the evaluation of the quality of a stabilized base fundation made using Portland cement, and another asphalt mixture called SUPERPAVE which is manufactured in heat, both of them used for the construction of the Quépos-Savegre stage of the “Costanera Sur” highway. This evaluation was carried out using the method of the Payment Based on the Quality. This is a statistical process which besides evaluating the existence of the data within the established limits, determines how reliable the distribution is within the given limits. This evaluation grants a result of for the quality between 0 and 1, that indicates the percentage of payment for the construction executed within certain term of qualification. Since it is a statistical method it requires of an effective tool to do the calculation, reason why for the accomplishment of the evaluation a sheet was programmed using Microsoft Office Excel, by means of this the engineering of the project and the administration of it was possible, allowing to us to obtain estimations of quality in real time and for each one of the periods of the invoicing. With the implementation of the programmed sheet in Excel, plus the gathering of data in field, the work performed for the months of June, July, August and September 2009 was realized, including all the stabilized basic and it the mixed asphalt. Results of quality were obtained of 99% and 100% respectively for the months of June and July for the stabilized base. Values of 85%, 99% and 98% were obtained respectively for the months of July August and September for the asphalt mixture. Finally an analysis is realized of the quality factors obtained and their consequences in the construction of the highway, besides the different behaviors produced by the method of evaluation in relation to the variation of the tests.
Proyecto de Graduación ( Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2010.
Keywords: Mezcla; Asfalto; Cemento; Calidad; Granulometría